Participant FIRST: Improving Communication With and Support For Participants in Trials that End Early. (20th December 2022) - Largent, Emily A.; Walter, Sarah; Edelmayer, Rebecca M.
Abstract: Background: In 2019, multiple AD/ADRD trials ended earlier than planned. Participants subsequently stepped forward explaining they first learned their trial ended via news coverage, rather than from a site investigator or research staff. As a result, the issue of participant notification—and the emotional impact of being in a trial that stops early—gained attention. This led to calls to identify better ways to communicate with and support participants after trials end early. Method: The multidisciplinary Participant F ollow‐Up I mprovement in R esearch S tudies and T rials (Participant FIRST) Work Group met throughout 2021. Members included research participants and study partners, clinical trialists and study personnel, as well as representatives from academia, industry, patient advocacy organizations, and the National Institutes of Health. The work group's goals were: (1) improving communication with research participants and study partners when trials end early and (2) identifying supports for those affected by early stopping. Results: The Participant FIRST Work Group identified 17 key recommendations. Pre‐trial recommendations focus on developing a patient‐centered communication plan and ensuring that participants and study partners understand early stopping (e.g., role of DSMBs, stopping rules) and securities laws that shape companies' announcements of trial stopping and, thus, how disclosure occurs. Mid‐trial recommendations focus on maintaining up‐to‐date contact information; helping participants and study partners build support networks; and reinforcing education on early stopping. Post‐trial recommendations focus on rapidly communicating with participants via multiple modalities; scheduling a personalized close‐out meeting to provide key information about the trial and discuss next steps; collaborating with patient advocacy organizations to provide support to participants (e.g., via a patient hotline); and ensuring that participants receive top‐line results. The work group calls for funders and sponsors to ensure adequate time and resources are available to communicate with and support participants when trials end early. Conclusion: Participants and study partners invest time, effort, and hope in their AD/ADRD research participation. The research community should hold itself accountable and take intentional steps towards better means of communicating with and supporting participants when clinical trials end early. The Participant FIRST recommendations are a practical guide for researchers and sponsors embarking on that journey.